Clinical application of third-generation dual-source CT-based dynamic imaging reconstruction for pulmonary embolism imaging - Kai Liao; Biao Ye; Xi Li; Wei Liu; Tongtong Jia; Zongbao Han; Ziyi Liang; Yongli Duan; Xiaoli Sun; Jianmei Zhang; Rengui Wang; Jiao Gong (Journal of Cardiothoracic Surgery)
Abstract Background To evaluate the clinical diagnostic value of third-generation dual-source CT for pulmonary embolism, focusing on the optimization of dual-source CT scanning with dynamic reconstruction in acute pulmonary embolism (PE) and various imaging manifestations. Methods Eighty-two patients with pulmonary embolism were enrolled and randomly divided into standard CT angiography (SCTA) and dynamic CT angiography (DCTA). DCTA patients were divided into dynamic CT angiography arterial phase (DCTAa), time phase Angiography reconstruction (TMIP-CTA), and 4D noise reduction TMIP-CTA according to the image reconstruction. The region of interest was selected in the region of the pulmonary trunk and its branches, respectively. The vessel CT value and image background noise (IN) of each subgroup were also determined, and the signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) were calculated. Simultaneously two radiologists performed a subjective evaluation of the quality of the picture images. Results The DCTA group had a lower contrast dose than the SCAT group, but the vessel CT value, IN, CNR, and SNR were significantly higher in the DCTA group compared with the SCTA group. CT of the vascular lumen was generally higher in all subgroups of DCTA than in SCTA, with the highest in the TMIP-CIA group. IN was significantly higher in both the DCTAa and TMIP-CTA groups than in the SCTA group. SNR and CNR were elevated in TMIP-CTA and 4D noise reduction TMIP-CTA compared to the SCTA group. In addition, the subjective image quality scores of the DCTA group were significantly higher than those of SCTA, and the 4D noise reduction TMIP-CTA had the most. However, the ED of the SCTA group was lower than that of the DCTA group. Conclusion 4D noise reduction TMIP-CTA based on DCTA reconstruction significantly improves the quality of pulmonary artery CTPA images and increases the clinical diagnostic rate, with potential for clinical dissemination.